2009
DOI: 10.1111/j.1582-4934.2009.00725.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of C-Kit Immunopositive Interstitial Cells of Cajal in the Human Stomach

Abstract: Interstitial cells of Cajal (ICC) include several types of specialized cells within the musculature of the gastrointestinal tract (GIT). Some types of ICC act as pacemakers in the GIT musculature, whereas others are implicated in the modulation of enteric neurotransmission. Kit immunohistochemistry reliably identifies the location of these cells and provides information on changes in ICC distribution and density. Human stomach specimens were obtained from 7 embryos and 28 foetuses without gastrointestinal diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 51 publications
5
40
0
1
Order By: Relevance
“…[68][69][70][71][72] In larger animals the muscle layers are much thicker than in rodents and it has been suggested that the function of septal ICC is to facilitate propagation of slow waves through the muscle layer. 65,68 Thus, ICC-SEP may provide a Purkinje cell-like function to facilitate slow wave propagation and coordinate excitation-contraction coupling through the entire thickness of the muscle.…”
Section: -62mentioning
confidence: 99%
“…[68][69][70][71][72] In larger animals the muscle layers are much thicker than in rodents and it has been suggested that the function of septal ICC is to facilitate propagation of slow waves through the muscle layer. 65,68 Thus, ICC-SEP may provide a Purkinje cell-like function to facilitate slow wave propagation and coordinate excitation-contraction coupling through the entire thickness of the muscle.…”
Section: -62mentioning
confidence: 99%
“…Therefore, antibodies against c-Kit are useful for the identification of ICC (2,3). c-Kit is a transmembrane tyrosine kinase receptor (rTK) and its activation by the stem cell factor (SCf) is essential for survival, maintenance of the phenotype and pacemaking activity of ICC (4). Apart from ICC, however, c-Kit and/or SCf are also expressed in a variety of normal tissues such as placenta and lung (16) and also in gastric carcinoma cell lines (17).…”
Section: Interstitial Cells Of Cajal (Icc)-like-c-kit Positive Cells mentioning
confidence: 99%
“…c-Kit is essential for the maintenance of normal hematopoiesis, melanogenesis and differentiation of mast cell and ICC [24]. Since c-Kit is known to maintain their proliferation, migration, and survival [4], the malfunction of c-Kit is thought to be associated also with a certain neoplastic disorders and gastric dysmotility in mucosa, microvilli, submucosal plexus and muscularis mucosa [1,21,22]. There is one more type of muscle in muscular layer of human gastric wall, also called oblique muscle, which is more prominent in fundus than corpus.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a blockade of c-Kit with neutralizing antibodies [11] and/or mutations of c-Kit or Steel [7] impair normal development of ICC in the myenteric plexus region (ICC-MY) of small intestine. It was reported that all subtypes of ICC in human stomach are been developed as early as 4 th month developmental stage with their specific functions [4]. To date, at least two types of major ICC have been identified in the GI tract: One is ICC-MY of myenteric region, and the other is a second population of ICC which are distributed outside the myenteric region and is abundant in deep muscular plexus through the muscle layers (intramuscular ICC, ICC-IM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation